Factors associated with the experience of patients presenting in pain to the emergency department. Issue 9 (9th August 2021) - Hughes, James A.; Alexander, Kimberley E.; Spencer, Lyndall; Yates, Patsy
Abstract: Aims and Objectives: This study aims to examine the association between person, environment, health and illness factors, pain care and the patient experience in the emergency department, guided by symptom management theory. Background: Current outcome measures of pain care in the emergency department focus on process measures such as the time taken to deliver analgesic medication. Patient‐reported outcomes of pain care are rare in emergency department literature and predominantly focus on patient satisfaction. Measuring overall patient experience is common, with extensive surveys undertaken in the United Kingdom, United States of America and Australia; however, these are not used as an outcome of pain care. Design: Prospective cohort study. Methods: One hundred and ninety patients arriving at a large, inner‐city adults‐only emergency department in moderate to severe pain were recruited to answer a modified version of the emergency department patient experience of care survey. Results: Fifteen factors were identified as influencing the patient experience of care when presenting in pain. These influences of patient experience included the emergency department environment, time to first analgesic medication and the provision of analgesic medication. Conclusions: In addition to pain care factors, there is a significant association between the emergency department environment—especially workload, throughput and patient placement—and the experience of patients who present in pain to the emergency department. Relevance to Clinical Practice: This study demonstrated an association between time to first analgesic medication and the patient experience of care. Providing timely care, including pain care, in emergency departments is difficult, but necessary to improve the patient experience of care.